Asset-Based Community Development in Vocational Schools Through Appreciative Inquiry (AI) and the BAGJA Model - Raindra Anggraeni Rosmalinda; Sobari Sobari (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the implementation of asset-based community development at SMK 2 LPPM RI Majalaya using qualitative methods through observation, interviews, and documentation. The findings reveal a significant gap between the availability of assets, including physical assets (workshops, laboratories), movable assets, and human assets (educators and students), and their collective mobilisation, attributed to the absence of a collaborative framework or "social contract" institutionalised within the school environment. To address this, the study integrated modern community development models such as Appreciative Inquiry and the BAGJA framework with local wisdom through the educational philosophy "Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karsa, Tut Wuri Handayani," resulting in culturally relevant and acceptable adaptations for the local community. The limitations of this study lie in its focus on a single case study and the use of qualitative methods alone, making it difficult to generalise the findings broadly. Therefore, further research with a more diverse scope and a mixed-methods approach is recommended to provide a more effective policy foundation for asset-based community development in vocational high schools